The genus Hypochaeris L. (Asteraceae) in Rio Grande do Sul, Brazil. - Azevêdo-Gonçalves, Cristiane F. (2007)
This study is a species inventory of Hypochaeris (Asteraceae) occurring in the Rio Grande do Sul state, Brazil. Twelve species are cited for this Brazilian State, and ten of them were found in the fieldworks and in the herbaria revisions: H. albiflora (Kuntze) Azevêdo-Gonç. & Matzenb., H. catharinensis Cabrera, H. chillensis (Kunth) Britton, H. lutea (Vell.) Britton, H. megapotamica Cabrera, H. neopinnatifida Azevêdo-Gonç. & Matzenb., H. tropicalis Cabrera, H. variegata (Lam.) Baker, H. radicata L., and H. glabra L. The two latter species are adventicious. Three natural hybrids were found: H. × microcephala (H. albiflora × H. chillensis), H. × confusa (H. albiflora × H. megapotamica), and H. × dolosa (H. chillensis × H. megapotamica). H. sellowii (Sch. Bip.) Cabrera and H. petiolares (Hook. & Arn.) Griseb. were not found in the present study, but they were cited in other studies. Two keys for species identification are presented including the three natural hybrids. Descriptions are accomplished by illustrations, considerations about their habitats, phenological data, geographic distribution, and other observations. Considerations about genus morphology are presented.